Pengaruh Taman Kambang Iwak Kecik Terhadap Tingkat Suhu dan Kelembaban di Masjid Raya Taqwa Palembang - Amin, Abdul Rachmad Zahrial; Anggraeni, Dhita Wahyu; Harrison, Steven (Universitas Muhammadiyah Palembang, 2024)
The people of Palembang city know Taman Kambang Iwak (fish pond) as a park for recreation, sports and social contact. Kambang Iwak is divided into two, namely the Kambang Iwak Besak Park (TKIB) and the Kambang Iwak Kecik Park (TKIK). Taman Kambang Iwak Kecik is behind the Taqwa grand mosque Palembang which has a pool that is ¼ the area of TKIB and has a green open space (RTH) which is quite small compared to TKIB. TKIK is surrounded by a 2.5 m wide pedestrian street that has many Tabebuya trees planted. With the fish pond and green open space, of course, the temperature and humidity of the environment affect the level of comfort in the room. Therefore this study aims to determine how much influence temperature and humidity have on the Taqwa Palembang Great Mosque. And descriptive analysis research method with an architectural approach. Data collection was carried out using Hobometers and anemometers. The data was analyzed by comparing it with the ASHRAE standard. It was found that the influence of temperature and humidity on TKIK had quite an effect on the level of comfort, especially during the day when the sun was hot which made the evaporation of the pool water enter the Raya Taqwa Mosque due to the wind blowing from the pool.